Implementation of the Nawacita Concept in the Development of Entrepreneurial Management in Indonesia: A Case Study of Micro, Small, and Medium Enterprises (MSMEs) - Hamdan Hamdan (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This article examines the implementation of the Nawacita concept in the development of entrepreneurial management in Indonesia, particularly in the Micro, Small, and Medium Enterprises (MSMEs) sector. The study aims to analyze how the principles of Nawacita, which include equitable development, economic strengthening, and community empowerment, can be applied in the context of MSMEs. Using a case study method, this article presents findings that demonstrate that the effective application of Nawacita can strengthen MSME management, enhance competitiveness, and expand market access. These findings are based on an analysis of various government initiatives and best practices that have been implemented by MSMEs across different regions in Indonesia. The research also identifies challenges faced by MSMEs in adopting the principles of Nawacita, including limited access to capital, inadequate infrastructure, and a lack of managerial training. As a result of this analysis, the article provides relevant policy recommendations for the future development of MSMEs, including increased government support in the form of training, access to technology, and the development of infrastructure that supports MSME growth. Thus, the implementation of Nawacita is expected to contribute to inclusive and sustainable economic growth in Indonesia.